Impact of flux gap upon dynamic resistance of a rotating HTS flux pump. (25th September 2015) - Jiang, Zhenan; Bumby, Chris W; Badcock, Rodney A; Sung, Hae-Jin; Long, Nicholas J; Amemiya, Naoyuki
Abstract: HTS flux pumps enable superconducting currents to be directly injected into a magnet coil without the requirement for thermally inefficient current leads. Here, we present results from an experimental mechanically rotating HTS flux pump employing a coated-conductor stator and operated at 77 K. We show the effect of varying the size of the flux gap between the rotor magnets and coated conductor stator from 1 to 7.5 mm. This leads to a corresponding change in the peak applied perpendicular magnetic field at the stator from approximately 350 to 50 mT. We observe that our experimental device ceases to maintain a measurable output at flux gaps above 7.5 mm, which we attribute to the presence of screening currents in the stator wire. We show that our mechanically rotating flux pump is well described by a simple circuit model which enables the output performance to be described using two simple parameters, the open-circuit voltage V oc and the internal resistance, R d . Both of these parameters are found to be directly proportional to magnet-crossing frequency and decrease with increasing flux gap. We show that the trend in R d can be understood by considering the dynamic resistance experienced at the stator due to the oscillating amplitude of the applied rotor field. We adopt a literature model for the dynamic resistance within our coated-conductor stator and show that this gives good agreement with the experimentally measured internal resistance of our flux pump.